A infância tecida: construindo a infância entre os teares e as escolas da Fábrica de Tecidos e Fiação Cedro e Cachoeira (1880-1915) - Manoel Julio de Paula (2010)
Inserted in the period 1880-1915, this dissertation presents the results of the study conducted in Companhia de Tecido e Fiação Cedro e Cachoeira, which had as its aim to analyze the primary schools created to children that worked in the mentioned factory, located in the city of Caetanópolis, Minas Gerais state. By analyzing the selected schools, one attempt to understand the working child schooling process and the feasibility strategies for the elementary instruction for the aforementioned population. Through this study, one longed to investigate, in that historical period, the childs spaces and instances of insertion and formation, highlighting the tensions between school and work. Trying to comprehend, thus, what infancy construction resulted from the overlapping of actions arouse out from the factory/school time. Therefore, one attempt to understand to what extent the experience brought by those children an experience forged from the clashes and struggles waged inside the factory environment would or would not influence the formation of subjects, no longer subjects of the factory, but of the school, a result of the dialogical relation between factory and school. Ideas and concepts developed by authors such as E.P. Thompson, Michel Foucault, Margareth Rago, Cristina Gouvêa, Viñao Frago, Faria Filho, among others were used in the analysis of documental sources. It was also used, to the development of this study, a vast documental source found in the Museu Décio Mascarenhas (Décio Mascarenhas Museum), such as Dossiers, Record Books, Handwritten Letters and Newspapers such as Gazeta de Paraopeba and Folha do Cedro. It was also of great value for this study the few but precious documents found in the Arquivo Público Mineiro (Public Archive of Minas Gerais State). Documents such as Educational Legislations, School Maps, Reports of the Public Inspectors of Education, Decrees of the Provisional Govern of the State of Minas Gerais, among others.